(untitled) (Research, Society and Development, 2025)
Introduction: Leprosy is an infectious disease caused by the Mycobacterium leprae complex, primarily affecting the skin and peripheral nerves. One of the main challenges in clinical management is the occurrence of leprosy reactions, acute inflammatory episodes that worsen the clinical condition and increase the risk of physical disability. Objective: To identify the clinical and epidemiological characteristics of patients who developed leprosy reactions at a referral center in the Brazilian Amazon between 2020 and 2025. Methods: This is a cross-sectional, retrospective, descriptive and documentary study of direct source with data from 20 patients with reactive episodes. Epidemiological, clinical, and therapeutic data were described and statistically analyzed. Results and Discussion: Among 94 patients diagnosed with leprosy, 20 (21.27%) developed reactional episodes, predominantly type II reactions (65%) and the Virchowian clinical form (70%). A predominance of male patients, multibacillary cases, and residents of the city of Belém was observed. Notably, reactions often occurred after the completion of multidrug therapy (MDT), even among patients with satisfactory treatment adherence, highlighting the need for long-term surveillance. Adverse effects were infrequent, with clofazimine being the most commonly implicated drug. No statistically significant association was found between sex, clinical form, treatment adherence, and type of reaction. Conclusion: The study identified a characteristic clinical-epidemiological profile of leprosy reaction cases: male, multibacillary patients, with the Virchowian form of the disease, adherent to treatment, and developing erythema nodosum leprosum after completing MDT.